Calculating the Center of Mass, and Introducing its Pattern of Changes for Adolescents in Format of Equations - Akbar Taherian; Masoumeh Shojaei; Afkham Daneshfar; Maryam Sharifdoust (Vesnu Publications, 2018)
Introduction: The center of mass is one of the most important features of the physical structure of the people, which is used in the balance tasks, screening in order to study the physical illnesses, talent acquisition, and designing safety and training devices. The aim of this study was to determine the center of mass, and investigating its changes in adolescents, to ultimately provide a fundamental, applied, and appropriate model based on the most important physical factors affecting it. Materials and Methods: Among 161134 adolescent students aged 12 to 18 years in Isfahan City, Iran, 384 adolescents were selected through cluster sampling. Height information in lying, standing, and sitting positions, was measured using standard meter, and mass of subjects was determined with a scale, as well as the center of mass with a measurement device based on the torque principles. The most important factors affecting the center of mass were identified using stepwise multivariate regression method, according to the necessary assumptions. Results: Sitting height to stature ratio, stature height, and sitting height were the most important factors predicting the center of mass in adolescents (P < 0.001). The average ratio of height of the center of mass to stature was calculated as 55.41% for adolescents. Conclusion: A model in the form of a formula was presented to estimate the center of mass of adolescents. This is a very good alternative to estimate the center of mass, rather than using hard, time-consuming, and expensive methods.